1996
DOI: 10.1046/j.1365-2958.1996.501417.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of competence for genetic transformation in Streptococcus pneumoniae by an auto‐induced peptide pheromone and a two‐component regulatory system

Abstract: The regulation of competence for genetic transformation in Streptococcus pneumoniae depends on a quorum-sensing system, but the only molecular elements of the system whose specific role have been identified are an extracellular peptide signal and an ABC-transporter required for its export. Here we show that transcription of comC, the gene encoding a predicted 41-residue precursor peptide that is thought to be processed and secreted as the 17-residue mature competence activator, increased approximately 40-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
384
3
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(398 citation statements)
references
References 27 publications
9
384
3
2
Order By: Relevance
“…We note that in Gram-positive bacteria that utilize peptide autoinducers to activate the quorum sensing systems, such as in lactobacilli (42), streptococci (43), and Bacillus subtilis (44), the autoinducing peptides are processed and secreted by proteins consisting of two domains, a proteolytic domain carrying out the enzymatic reaction, and an ATP-binding domain forming an ATP-binding cassette transporter that exports the mature autoinducing peptide (45,46). These proteins are encoded by genes in the same operons as those that encode propeptides and the two component signal transduction systems.…”
Section: Discussionmentioning
confidence: 99%
“…We note that in Gram-positive bacteria that utilize peptide autoinducers to activate the quorum sensing systems, such as in lactobacilli (42), streptococci (43), and Bacillus subtilis (44), the autoinducing peptides are processed and secreted by proteins consisting of two domains, a proteolytic domain carrying out the enzymatic reaction, and an ATP-binding domain forming an ATP-binding cassette transporter that exports the mature autoinducing peptide (45,46). These proteins are encoded by genes in the same operons as those that encode propeptides and the two component signal transduction systems.…”
Section: Discussionmentioning
confidence: 99%
“…Such a three-component regulatory system involving a pheromone peptide and a cognate signal-transducing network not only seems to be frequently used in the regulation of bacteriocin production from different species (Kleerebezem et al, 1997), but has also been found to play key roles in other biological pathways. Examples are the com and agr systems that control competence development in streptococci and the expression of virulence proteins during stationary growth phase in Staphylococcus aureus, respectively (Novick et al, 1995 ;Pestova et al, 1996). For the sakacin A system, however, the question remains whether the temperature ' switch ' has some function in vivo, and\or if the system works as a quorum-sensing device as suggested for the nisin system (Kuipers et al, 1995 ;Kleerebezem et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of bacteriocin production in L. sake LTH673 bears striking similarities to the regulation of competence for genetic transformation in Streptococcus pneumoniae (Hå varstein et al, 1995b;1996;Pestova et al, 1996;Cheng et al, 1997). Both regulatory mechanisms involve an unmodified, basic peptide pheromone whose secretion is directed by a typical double-glycine leader peptide (Håvarstein et al, 1995b) and whose gene is co-transcribed with a two-component signal transduction system (Cheng et al, 1997).…”
Section: Discussionmentioning
confidence: 99%